2010
DOI: 10.1063/1.3478717
|View full text |Cite
|
Sign up to set email alerts
|

First-principles investigations on electronic, elastic and optical properties of XC (X=Si, Ge, and Sn) under high pressure

Abstract: An investigation on electronic, elastic, and optical properties of XC ͑X = Si, Ge, and Sn͒ under high pressure has been conducted using first-principles calculations based on density functional theory with the plane wave basis set as implemented in the CASTEP code. Our results demonstrate that the sequence of the pressure-induced structure transition of these compounds is from zincblende-type ͑B3͒ to NaCl-type ͑B1͒ structure. The calculated lattice constants and transition pressures are reported, which are in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 27 publications
5
55
0
2
Order By: Relevance
“…It is noticed from the plot that our approach has predicted correctly the relative stability of competitive crystal structures, as the values of ∆G are positive. The magnitude of the discontinuity in volume at the transition pressure is obtained from the phase diagram and tabulated in table 2, which is in good agreement with those revealed from other theoretical [3] works for all the compounds.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…It is noticed from the plot that our approach has predicted correctly the relative stability of competitive crystal structures, as the values of ∆G are positive. The magnitude of the discontinuity in volume at the transition pressure is obtained from the phase diagram and tabulated in table 2, which is in good agreement with those revealed from other theoretical [3] works for all the compounds.…”
Section: Resultssupporting
confidence: 75%
“…Further, we found that the P t of GeC is higher than that of SiC. Such an observation could be due to existence of the d-core states in Ge as compare to Si, results in an extra repulsion, which leads to a higher transition pressure [3]. The consistency between band structure calculations data and the present lattice model calculation is attributed to the formulated effective interionic potential which considers the various interactions.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Among these, * Electronic address: mogulkoc@science.ankara.edu.tr monolayer honeycomb lattice of SnC (two dimensional binary compound of carbon and tin atom) shows planar structure where atoms are located on the same plane with indirect energy band gap between Γ and K high symmetry points with lower SOC according to stanene. Even there is no experimental work related this material, some theoretical calculations were devoted to electronic, elastic and optical properties of bulk [17,18] and monolayer [11,13,19] SnC. An indirect-direct band gap transition of SnC was predicted through adatom decoration [11] and applied strain [13] in the scheme of DFT.…”
Section: Introductionmentioning
confidence: 99%
“…These expressions have been widely used in previous first-principles calculations of the optical properties [21,[23][24][25][26][27][28][29][30].…”
Section: Computational Detailsmentioning
confidence: 99%